The Oxford handbook of industrial hubs and economic development - Oqubay, Arkebe; Lin, Justin Yifu, 1952- (Oxford handbooks online., 2020)
Industrialization supported by industrial hubs has been widely associated with structural transformation and catch-up. But while the direct economic benefits of industrial hubs are significant, their value lies first and foremost in their contribution as incubators of industrialization, production and technological capability, and innovation. This handbook adopts an interdisciplinary approach to examine the conceptual underpinnings, review empirical evidence of regions and economies, and extract pertinent lessons for policy reasearchers and practitioners on the key drivers of success and failure for industrial hubs.- Resumé vydavatel